Primary central nervous system post-transplant lymphoproliferative disorder after allogeneic stem cell transplantation: a case report - Tugend, Margaret; Dattero, Jordan; Shore, Tsiporah; Korobeynikov, Vladislav; Sekula, Raymond F. (Frontiers in Oncology, 2024)
Purpose Primary central nervous system, diffuse large B-cell lymphoma, post-transplant lymphoproliferative disorder in the cerebellopontine angle after an allogeneic stem cell transplantation has never been reported in the literature. Typically, diffuse large B-cell lymphoma is non-polyploid. We report the first case of a patient with polyploid post-transplant lymphoproliferative disorder in the cerebellopontine angle who presented with back pain. Case presentation A 45-year-old man with a history of nodular sclerosing classic Hodgkin lymphoma stage IIB treated with systemic chemotherapy, external radiation and autologous stem cell transplant and double umbilical cord allogeneic transplant presented with several weeks of back pain. He was found to have a small right cerebellopontine angle mass thought to be consistent with a meningioma. Patient presented again two weeks later with acute onset of severe headache, right sided ptosis, right facial numbness, weakness and possible seizure event. Repeat MRI scans showed an interval and significant increase of the right cerebellopontine angle lesion. Biopsy of the cerebellopontine angle lesion was planned with suspicion of lymphoma. Intraoperative pathology consultation findings were not consistent with an acoustic neuroma, meningioma, or epidermoid cyst. Lymphoma could not be definitively identified by intra-operative frozen section. However, it was suspected, and a portion of fresh specimen was submitted for flow cytometry analysis. A near total resection of the tumor and decompression of the brainstem was achieved. Final pathologic analysis was positive for post-transplant lymphoproliferative disorder, monomorphic type, diffuse large B-cell lymphoma, non-germinal center B-cell type, EBV+, post-transplant (allogeneic stem cell) setting (post-transplant lymphoproliferative disorder (PTLD), monomorphic type, diffuse large B-cell lymphoma, non-germinal center B-cell type (non-GCB), EBV-positive under pre-2022 WHO terminology). The patient began a high-dose methotrexate-based regimen (the MATRIX regimen). Conclusions Our case illustrates an unusual presentation of post-transplant lymphoproliferative disorder in the cerebellopontine angle in a patient with a remote history of allogeneic stem cell transplantation. It demonstrates the importance of keeping primary central nervous system post-transplant lymphoproliferative disorder on the differential for patients who present with back pain or headache that have a history of allogeneic stem cell transplant.